The influence of African traditional religion on modernity: a case study of Ifá divination and contemporary gospel music in Yorùbá society, Nigeria (2023)
This paper seeks to examine the influence of African traditional religion on modernity in relation to music which is a universal language that everyone, old and young understands. Regardless of the population, every community in the world can boast of one form of music or the other especially traditional music. It is a social and religious activity that fosters and reinforces communal unity. Unfortunately, the attitude the contemporary Yorùbá people are displaying towards traditional music is not favourable enough, most especially gospel music in Yorùbá society. They are either unaware or pretending to be unaware that elements of these African traditional music form the basis of and can still be found in their music, particularly Ifá music and verses. However, the most unfortunate aspect of the issue is that if these songs are rendered by the traditionalists, they are frowned at but nothing seems bad if they are found and sung in gospel music. The questions one may ask then are: why the critique that these songs are ‘Orin ayé’ [worldly music] when these same songs are found or sung in a different forms and atmosphere? Are they not passing same message across to the same audience? These are some of the questions that this paper tries to address. Textual analysis of some selected Ifá verses and songs were done. Also, ten Ifá priests and ten gospel singers were interviewed and their responses content-analysed. The study discovered that, though music is in multicolour form (different religious perspectives), yet, it should be realised that music, regardless of its background is out to achieve the goal of communicating moral teaching and educate the society in diverse ways beyond entertainment as shown in some of the examples cited in the paper.